Adaptive Civics Learning Design Training: Accommodating the Diversity of Student Characteristics in the Formation of Character and Pancasila Values - Dimyati, Endang; Sudarman, Otang; Nani, Nani; Maulani, Yana; Ginanjar, Gelar; Livani, Lumi Puspa; Mulyati, Helma; Sarimudaha, D. Cacap; Herawati, Wanti; Susilawati, Ida Farida; Juniar, Nizar Dwi; Sutiani, Ai (Indonesian Journal of Community Empowerment (IJCE), 2024)
This community engagement initiative centered on a specialized workshop concerning Adaptive Civic Education (PKn) Instructional Design. Its primary objective was to enhance pedagogical competencies among PKn educators in Garut Regency, enabling them to effectively accommodate the diverse learning characteristics of students in the context of character development and the internalization of Pancasila values. The program yielded a statistically significant improvement in participants' conceptual understanding and practical application of adaptive learning principles and instructional differentiation strategies. Direct engagement in the design of adaptive lesson plans (RPP) served as empirical evidence of their enhanced ability to translate theoretical constructs into practical pedagogical tools. High levels of active participation and collaborative engagement among the educators were consistently observed, underscoring the program's perceived relevance and efficacy in professional empowerment. While marginal variances in technological proficiency were noted among a minority of participants regarding the full integration of adaptive methodologies, the overarching outcome was unequivocally positive. This intervention critically highlights the imperative for sustained professional development and the establishment of robust professional learning communities to ensure the enduring integration of these innovative pedagogical approaches, thereby elevating the quality of PKn instruction across the region.